PERSEPSI MASYARAKAT TERHADAP KAWASAN KONSERVASI PENYU DI PANTAI PASIR JAMBAK KOTA PADANG - Maftukhoh Cergia; Harfiandri Damanhuri; Suparno Suparno (Sekolah Tinggi Teknologi Industri Padang, 2022)
Knowledge is a number of symptoms that humans encounter, acquire, and absorb through clever observation. Attitude is opinions of the person on environmental issues. Action is deeds people do all their live to achieve a particular purpose. Knowledge, attitude, and action to refinements of turtle sanctuaries is development of ecotourism in Pasir Jambak Beach, Padang City reviewed as future assessments to the proper benefit society and stakeholders. This research’s purpose to explain public’s perceptions about protection of turtles. The kind of research was the quantitative method, in which responders produced questions as a sample and then data obtained was analyzed using SPSS. The location and time of research on date October 4th to November 4th at Pasir Jambak Beach, Padang City. Most of questions was generated from perceptions of three groups rated very well for turtle breeding evaluations. Zscore significance 5% (1,96) provided that the normal data is < + 1,96 (Sig. 0,05 as to Sig. 0,01) so that from research data obtained questionnaire data from respondents regarding perceptions towards turtle conservation with normal distribution or said to be evenly distributed. Thus, public's perceptions of turtle conservation has an important relationship in responding to a problem in the surrounding environment.